Predictive analysis of catecholamines and electrolytes for recurrence of orthostatic intolerance in children - Chang, Lujie; Peng, Lu; Liu, Jianglin; Wang, Minmin; Li, Meng; Kong, Qingyu; Zhao, Haizhao; Zhao, Cuifen (Frontiers in Pediatrics, 2023)
Background: Orthostatic intolerance (OI) is usually mediated by the autonomic nerve, and most often happens in the upright position, but can also occur in other positions and can be relieved by lying down, while likely to have another attack after relief. In the current study, we aimed to evaluate the predictive effect of catecholamines and electrolytes on the recurrence of OI in children.Children who were diagnosed with vasovagal syncope (VVS), postural tachycardia syndrome (POTS), and VVS combined with POTS were enrolled in this retrospective study, and were followed up after one-year physical treatment.Catecholamines in urine during 24 hours, renin, angiotensin II, aldosterone in plasma, and electrolytes in both blood and urine in the morning were tested. Multivariate analysis and a ROC curve were used to validate the prediction effect.Results: In the VVS cohort, the 24-hour urine adrenaline (AD) and norepinephrine (NE) levels of the non-recurrence group were lower than those of the recurrence group, with significant difference (P < 0.05). Different content can also be witnessed in POTS cohort that urine of the non-recurrence group contained lower sodium and chlorine. As for the VVS+POTS cohort, non-recurrence group has lower AD and NE and higher potassium and phosphorus in urine, the difference of which proved prominent as well.The study provides further evidence that AD, NE, and electrolytes in urine are promising factors that are closely related to the recurrence of OI in children. The integrated evaluation system merging AD and NE may have better predictive ability.